Efficacy Study of Eco-Friendly Bleaching Agent for Skeleton Preservation in Animal Skeleton - Umami, Muhimatul (Universitas Atma Jaya Yogyakarta, 2024)
The currently used bleaching materials in skeletal preservation are hydrogen and carbamide peroxide materials with specific concentrations and techniques that impact environmental sustainability. This research describes a simple and eco-friendly technique for preserving skeletons. This research used a qualitative approach. Data were collected through observation and documentation. The collected data were analyzed descriptively. The results show that natural extracts, such as lemon combined with baking soda and commercial bleaching cloth agent, can bleach the skull and bone to preserve the skeleton. The commercial bleaching cloth agent is more capable of bleaching animal skulls and bones to preserve skeletons than natural extracts combined with baking soda do; however, the result is more brittle skeletons. Although specimens in lemon extract combined with baking soda solution more slowly clean and bleach skeleton than commercial bleaching solution, skeletal animals have bond strength and environment-friendly processes. This study recommends that an eco-friendly bleaching agent for skeletal preservation should be applied because it can cope with biological practices about osteology and other science subjects.